Frequencies of Single Nucleotide Polymorphisms in Cytochrome P450 Genes (CYP1A2, 2A6, 2B6, 3A4 and 3A5) in a Rwandan Population: Difference to Other African Populations - Bienvenu, Emile; Swart, Marelize; Dandara, Collet; Ekman, Agneta; Abelo, Angela; Wonkam, Ambroise; Ashton, Michael (Current Pharmacogenomics and Personalized Medicine, 2013)
The cytochrome P450 (CYP450) enzymes play a key role for interindividual variability in drug response. No comprehensive pharmacogenetic data are yet available for the Rwandan population in regards to single nucleotide polymorphisms in CYP450s of major importance for personalized medicine. This study investigated the genotype and allele frequencies with respect to relevant SNPs for CYP1A2, CYP2A6, CYP2B6, CYP3A4 and CYP3A5 genes in Rwandan subjects (n=80). Results were compared with data from South African and Cameroonian populations using Pearson’s Χ 2 and Fisher’s Exact statistical tests. Genetic variation was observed in 11 out of the 13 SNPs in the above CYP450 genes. There were significant differences in the distribution of the allelic variants when the Rwandan sample was compared to the Cameroonian and the South African groups, with respect to CYP2A6 1093G>A SNP (P=0.0033 and 0.019, respectively) and CYP3A4 -392A>G SNP (P=0.0001 and 0.0084, respectively). The distribution of the CYP1A2 -163C>A SNP differed between the Rwandans and the South Africans (P=0.0001), and CYP3A5 6986A>G SNP between the Rwandan and the Cameroonian subjects (P=0.017). The polymorphisms CYP2B6 516G>T and 785A>G did not show significant differences (P>0.05) between the Rwandans, Cameroonians and South Africans in the distribution of the 516T and the 785G variants. This is the first study evaluating the allele and genotype frequencies of these key CYP450 genes in Rwandan subjects. The results demonstrate the need to further characterize individual African populations with respect to genetic variations in order for personalized medicine to be realized among Africans. These data will also help illuminate the future planning of pharmacodynamic studies aimed at associations of these pharmacogenetic variants with drug safety and efficacy in Rwanda.
Keywords: population